THE EFFECT OF LIQUIDITY, PROFITABILITY, LEVERAGE AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH DIVIDEND POLICY AS A MODERATING VARIABLE (EMPIRICAL STUDY IN LQ45 COMPANIES LISTED ON THE IDX) - Mentalita, Hotma (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aimed to analyze the effect of liquidity, profitability, leverage and corporate social responsibility on firm value with the dividend policy as a moderating variable (Empirical Study on companies listed as LQ45 in Indonesia Stock Exchange) in 2011 - 2016. This type of research is explanatory research method. Sampling used is purpossive on the criteria which companies consistently listed during the period of research. There are 21 companies observed out of 309 companies as population. The method of data collection is documentation. Method of data analysis is  panel data regression analysis. The results of this study showed that simultaneously liquidity, profitability, leverage and corporate social responsibility have significant effect on firm value. Partial test showed that liquidity has no effect on firm value, profitability positively and signifficantly affect the firm value, leverage also has no effect on firm value, and corporate social responsibility has significant effect on firm value  Moderating test with the residual test showed the dividend policy has not proved as moderating variable that may moderate the relationship of liquidity, profitability, leverage and csr with the firm value of the companies listed on LQ45 in the Indonesia Stock Exchange.